Protein sequence for finishing swine - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Using. sixty barrows and gilts, we evaluated five protein sequences for finishing swine. Pigs fed rations containing 16% protein until they weighed 140 lbs., then 12% protein until they weighed 190 lbs., and there after 10% protein (ABC) until market weight gained significantly slower and at a greater cost per lb. of gain than did pigs in any of the other sequences. The cheapest cost per lb. of gain was observed for those pigs fed a 16% protein diet until they weighed 140 lbs. and then a 12% protein diet (ABB) until marketed at 240 lbs. Pigs with the leanest carcasses, largest loin eye, and greatest percentage of lean cuts were those fed a 16% protein diet (AAA) throughout the finishing trial. Pigs fed 16% protein diet to 140 lbs., 12% protein diet to 215 lbs. and then a 10% diet to market weight performed similarly to the ABB sequence group, as did pigs fed 16% protein diet to 190 lbs. and then a 10% ration (AAC) to market weight. Because of high feed costs, swine feeding programs may have to be evaluated continually to determine the most economical gain, which may or may not be compatable with superior rate of gain or carcass merit.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Protein; Finishing pigs; Barrows; Gilts; Weight gain